A genetic dissection of breed composition and performance enhancement in the Alaskan sled dog - Runstadler Jonathan; Parker Heidi G; Huson Heather J; Ostrander Elaine A (BMC Genetics, 2010)
Abstract Background The Alaskan sled dog offers a rare opportunity to investigate the development of a dog breed based solely on performance, rather than appearance, thus setting the breed apart from most others. Several established breeds, many of which are recognized by the American Kennel Club (AKC), have been introduced into the sled dog population to enhance racing performance. We have used molecular methods to ascertain the constitutive breeds used to develop successful sled dog lines, and in doing so, determined the breed origins of specific performance-related behaviors. One hundred and ninety-nine Alaskan sled dogs were genotyped using 96 microsatellite markers that span the canine genome. These data were compared to that from 141 similarly genotyped purebred dog breeds. Sled dogs were evaluated for breed composition based on a variety of performance phenotypes including speed, endurance and work ethic, and the data stratified based on population structure. Results We observe that the Alaskan sled dog has a unique molecular signature and that the genetic profile is sufficient for identifying dogs bred for sprint versus distance. When evaluating contributions of existing breeds we find that the Alaskan Malamute and Siberian Husky contributions are associated with enhanced endurance; Pointer and Saluki are associated with enhanced speed and the Anatolian Shepherd demonstrates a positive influence on work ethic. Conclusion We have established a genetic breed profile for the Alaskan sled dog, identified profile variance between sprint and distance dogs, and established breeds associated with enhanced performance attributes. These data set the stage for mapping studies aimed at finding genes that are associated with athletic attributes integral to the high performing Alaskan sled dog.